Validation of a brief scale to assess ambulatory patients' perceptions of reading visit notes: a scale development study. Issue 10 (20th October 2020) - Wright, Julie A; Leveille, Suzanne G; Chimowitz, Hannah; Fossa, Alan; Stametz, Rebecca; Clarke, Deserae; Walker, Jan
Abstract : Objectives: To develop and evaluate the validity of a scale to assess patients' perceived benefits and risks of reading ambulatory visit notes online (open notes). Design: Four studies were used to evaluate the construct validity of a benefits and risks scale. Study 1 refined the items; study 2 evaluated underlying factor structure and identified the items; study 3 evaluated study 2 results in a separate sample; and study 4 examined factorial invariance of the developed scale across educational subsamples. Setting: Ambulatory care in three large health systems in the USA. Participants: Participants in three US health systems who responded to one of two online surveys asking about benefits and risks of reading visit notes: a psychometrics survey of primary care patients, and a large general survey of patients across all ambulatory specialties. Sample sizes: n=439 (study 1); n=439 (study 2); n=500 (study 3); and n=250 (study 4). Primary and secondary outcome measures: Questionnaire items about patients' perceived benefits and risks of reading online visit notes. Results: Study 1 resulted in the selection of a 10-point importance response option format over a 4-point agreement scale. Exploratory factor analysis (EFA) in study 2 resulted in two-factor solution: a four-item benefits factor with good reliability (alpha=0.83) and a three-item risks factor with poor reliability (alpha=0.52). The factor structure was confirmed in study 3, and confirmatory factor analysis of benefit items resulted in an excellent fitting model, X 2 (2)=2.949; confirmatory factor index=0.998; root mean square error of approximation=0.04 (0.00, 0.142); loadings 0.68−0.86; alpha=0.88. Study 4 supported configural, measurement and structural invariance for the benefits scale across high and low-education patient groups. Conclusions: The findings suggest that the four-item benefits scale has excellent construct validity and preliminary evidence of generalising across different patient populations. Further scale development is needed to understand perceived risks of reading open notes.